2004
DOI: 10.1128/jcm.42.4.1637-1640.2004
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Selective Differential Broth for Isolation of Vancomycin-Resistant Enterococcus from Fecal Material

Abstract: Studies have shown that vancomycin broth enrichment is superior to direct plating for the detection of vancomycin-resistant enterococcus (VRE), but vancomycin selective broth is not generally commercially available. We developed an easy-to-prepare VRE selective differential broth and compared it to direct plating on bile esculin azide (BEA) agar for the isolation of VRE from fecal samples. A total of 528 consecutive rectal swabs and stools were inoculated onto BEA agar and into BEA broth with vancomycin at a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 25 publications
2
12
0
3
Order By: Relevance
“…The sensitivities of the chromID VRE and BEAv media were similar under various conditions of use (Table 1, P Ͼ 0.05). The rate of VRE detection was significantly increased by the enrichment step, as previously demonstrated (7,11,16). However, fecal carriage of these VRE was transitory in patients and this increased sensitivity may not be essential for the management of most outbreaks (4).…”
supporting
confidence: 57%
“…The sensitivities of the chromID VRE and BEAv media were similar under various conditions of use (Table 1, P Ͼ 0.05). The rate of VRE detection was significantly increased by the enrichment step, as previously demonstrated (7,11,16). However, fecal carriage of these VRE was transitory in patients and this increased sensitivity may not be essential for the management of most outbreaks (4).…”
supporting
confidence: 57%
“…A summary of these studies is presented in Table 3. The differences in studied populations, laboratory methods, and study design make a head-to-head comparison difficult, but several conclusions can be made: (i) among agar-based methods, the use of carbapenem disks on MacConkey plates appears to be the least sensitive, and (ii) unlike screening for vancomycin-resistant enterococci (18), enrichment in broth was not superior to direct plating (13). Our study adds to the current literature the direct comparison of MacI with two previously described agarbased methods, along with an examination of the analytic sensitivity of these methods in detecting various types of CRE strains.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this study is that an enrichment broth was not used and may have affected the sensitivity of VRE isolation by culture. While some studies have demonstrated that broth enrichment may increase the VRE detection by 10 to 30% (10,12), the number of specimens positive for vanB by PCR yet negative by culture far exceeds what one would expect even if an enrichment broth was used.…”
mentioning
confidence: 97%